Ordered compactification of totally ordered spaces - D. C. Kent; T. A. Richmond (International Journal of Mathematics and Mathematical Sciences, 1988)
A complete description of the T2-ordered compactifications of a totally ordered space X is given in terms of the simple and essential singularities.